2015
DOI: 10.3390/nu7105427
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Antipsychotic Treatment with the Amino Acid Sarcosine Influences Proton Magnetic Resonance Spectroscopy Parameters in Left Frontal White Matter in Patients with Schizophrenia

Abstract: Dysfunction of the glutamatergic system, the main stimulating system in the brain, has a major role in pathogenesis of schizophrenia. The frontal white matter (WM) is partially composed of axons from glutamatergic pyramidal neurons and glia with glutamatergic receptors. The natural amino acid sarcosine, a component of a normal diet, inhibits the glycine type 1 transporter, increasing the glycine level. Thus, it modulates glutamatergic transmission through the glutamatergic ionotropic NMDA (N-methyl-d-aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 102 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…Evidence that GlyT1 substrates like sarcosine and inhibitors of GlyT1 indeed have diverging effects on CNS function despite comparable effects of the extracellular glycine concentration come from studies in the context of psychosis. Here, add-on treatment of patients with a high dose of sarcosine resulted in a significant amelioration of especially negative symptoms ( Strzelecki et al, 2015 ), whereas bitopertin (at least in the Phase III clinical trials) was shown to be not effective ( Bugarski-Kirola et al, 2016a ). Whether these differences are a result of the different mechanism of action on GlyT1 or a result of the different substrate specificity – sarcosine, e.g., functions as a partial agonist on GlyRs, as well as NMDAR, but also possibly effects system A ( Javitt et al, 2005 ) and system N ( Hamdani et al, 2012 ) – is unclear at present, and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that GlyT1 substrates like sarcosine and inhibitors of GlyT1 indeed have diverging effects on CNS function despite comparable effects of the extracellular glycine concentration come from studies in the context of psychosis. Here, add-on treatment of patients with a high dose of sarcosine resulted in a significant amelioration of especially negative symptoms ( Strzelecki et al, 2015 ), whereas bitopertin (at least in the Phase III clinical trials) was shown to be not effective ( Bugarski-Kirola et al, 2016a ). Whether these differences are a result of the different mechanism of action on GlyT1 or a result of the different substrate specificity – sarcosine, e.g., functions as a partial agonist on GlyRs, as well as NMDAR, but also possibly effects system A ( Javitt et al, 2005 ) and system N ( Hamdani et al, 2012 ) – is unclear at present, and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the drug-naïve participants (5/11) were considered responders but none of the non-naïve patients responded. Strzelecki et al (2015) [75] correlated clinical improvement associated with adjunct sarcosine 2 g/d for 6 months with neuroimaging findings. Their result indicated add-on sarcosine was associated with statistically significant improvement in PANSS negative and general psychopathology scores in comparison to placebo.…”
Section: Sarcosinementioning
confidence: 99%
“…Their result indicated add-on sarcosine was associated with statistically significant improvement in PANSS negative and general psychopathology scores in comparison to placebo. Furthermore, using Proton nuclear magnetic resonance (H-NMR) spectroscopy, they demonstrated reversal of the pathological increase in glutamatergic transmission in the left frontal lobe [75] and hippocampus [70] as well as increased markers of neuron viability and neuroglial activity in the left dorsolateral prefrontal cortex (DLPFC) [76].…”
Section: Sarcosinementioning
confidence: 99%
“…Higher concentrations of glycine lead to an increase of the N‐methyl‐D‐aspartate (NMDA) receptor activity (Millan, ). Pharmacological interventions concerning the NMDA receptor either based on NMDA co‐agonists, such as glycine, D‐serine or D‐cycloserine, or GlyT1 inhibitors, such as sarcosine or bitopertine, decrease negative symptoms in schizophrenia (Balu, ; Hirayasu et al, ; Strzelecki et al, ); those based on ketamine, an NMDA antagonist, decrease depressive symptoms in affective disorders (Iadarola et al, ; Zarate et al, ).…”
Section: Introductionmentioning
confidence: 99%